2016
DOI: 10.1093/intqhc/mzw079
|View full text |Cite
|
Sign up to set email alerts
|

Improving inpatient environments to support patient sleep

Abstract: The research is hard to consolidate due to the multitude of independent variables and outcome metrics, but overall points to the potential for making meaningful improvements in the quality of patient sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 60 publications
3
60
0
4
Order By: Relevance
“…Nonpharmacological alternatives such as providing ear plugs and eye masks, changing the light and sound environment, and reducing nursing care activities that disrupt sleep as a first line treatment for transient sleep disturbances in the hospital environment can reduce the number of patients who experience sleep‐inducing drugs for the first time in the hospital. Whether these strategies can also reduce the number of individuals who become long‐term hypnosedative drug users in old age and how it is possible to reduce the patient wish to continue sleep‐inducing drugs after discharge should be topics for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Nonpharmacological alternatives such as providing ear plugs and eye masks, changing the light and sound environment, and reducing nursing care activities that disrupt sleep as a first line treatment for transient sleep disturbances in the hospital environment can reduce the number of patients who experience sleep‐inducing drugs for the first time in the hospital. Whether these strategies can also reduce the number of individuals who become long‐term hypnosedative drug users in old age and how it is possible to reduce the patient wish to continue sleep‐inducing drugs after discharge should be topics for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the effectiveness of using eye mask in improving sleep quality in hospitalized patients in general medical wards, post anesthesia care units as well as in intensive care units [33][34][35]. A review also demonstrated that changing the sound and light environment appeared to be effective in improving sleep in hospitals [36]. Great variance of the sleep outcome reported, multitude of independent variables, and outcome metrics of the current available studies made it difficult to conclude.…”
Section: Sleep Disordersmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Fortunately, some recent interventions have been proposed to improve sleep quality during hospitalization and have shown promising results. 11 No data are currently available on subjective sleep quality in the emergency department (ED). The main objective of this study was to assess the subjective quality of patient nighttime sleep in the ED and its associated factors.…”
Section: Introductionmentioning
confidence: 99%